Limberg Flap Procedure for Managing Sacrococcygeal Pilonidal Sinus Disease: our Experience (Journal of Dhaka Medical College, 2021)
Background: Sacrococcygeal pilonidal sinus is a common morbid disease in young adult patients with high recurrence rate. There are several surgical procedures for managing pilonidal sinus. The present study aims to evaluate the efficacy of limberg flap reconstruction surgery for the management of sacrococcygeal pilonidal sinus.Methods: A prospective study was conducted over a period of more than two years from January 2017 to June 2019. A total of 21 patients were included in this study. All patients underwent Limberg flap reconstruction. Data collected in data collection sheet regarding demographic data, post operative complications and analyzed in tabulated form.Results: Total 21 patients were included in our study. Age ranged from 20-50 years. Male were 18(85.71%) and female were 3(14.29%). Post operative complications were seroma 2(9.52%), wound infection 1(4.76%). But no flap necrosis and recurrence had occurred.Conclusion: Limberg flap for reconstruction of the defect after excision of sacroccoccygeal pilonidal sinus is an effective and safe technique with low complication rate.J Dhaka Medical College, Vol. 29, No.1, April, 2020, Page 38-40